The importance of visual language in educational videos - Makhlouf Akl, Antonio; Iñigo Dehud, Laura Silvia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
As a result of the dizzying evolution of digital media, the image has proliferated and there is easy access to the production of visual materials. Video, as a learning object, is a powerful tool, however, the lack of visual literacy has reduced the quality of the graphic materials produced. The general objective of this research is to analyze how and why the application of Visual Language standards in didactic videos optimizes and contributes positively to their understanding and to their function as a teaching and learning tool.